Urban Road Landscape Design and Digital Twin Simulation Modeling Analysis - Nan Yin; Minghui Cai (Discrete Dynamics in Nature and Society)
The concept of a digital twin (DT) has lately become popular in the domains of urban planning and managed services. Densification and competing use of urban highways will result from an increase in local and foreign workers in the next years. The MFFO (modified fruit fly optimization) method for large-scale data transfer is presented in this study. The first step is to get data from the internet. A map-matching technique is also given in this section of preprocessing. Validated data may then be loaded into DT to reproduce processes. The results of DT are included in the landscape architecture and the server of the urban road network. The server’s data may be improved by modernized fruit fly optimization (MFFO) to enhance the transmission control protocol (TCP). Finally, the performances from the urban road design are examined and matched with existing techniques. The results are shown in the MATLAB simulation software. The results reveal that the proposed system increased the accuracy of digitalized urban road data protection for all secret information while also taking lesser time to execute than existing methods.